New method for determination of diclofenac sodium by High Performance Liquid Chromatography (Tikrit Journal of Pharmaceutical Sciences, 2023)
In this study a simple, coast effective and direct simple High Performance Liquid Chromatography (HPLC) method has been developed for the determination of diclofenac sodium in it's pure form and different pharmaceutical preparations. Standard diclofenac sodium and its dosage forms were supplied from Ninava State Company For Drug Industries and Medical Appliances (NDI). HPLC method was developed by using mobile phase which was composed of a mixture of HPLC grade (methanol, acetonitrile and deionized water)in the ratio of (60:20:20) respectively. Separation has been completed within 2 min. Calibration curve was linear, coefficient correlation was found to be 1.00 at a concentration of (0.25-4.0 µg.ml-1). The relative standard deviation (RSD) was found to be >1.2%. The proposed method was successfully applied for the determination of diclofenac sodium in its pure form and different pharmaceutical preparations (injection, tablets, eye drops, suppositories and gel) without using buffer system and there is no inference with additives.